Interpreting the three‐dimensional orientation of vascular canals and cross‐sectional geometry of cortical bone in birds and bats. Issue 6 (8th March 2018) - Pratt, Isaac V.; Johnston, James D.; Walker, Ernie; Cooper, David M. L.
Abstract: Cortical bone porosity and specifically the orientation of vascular canals is an area of growing interest in biomedical research and comparative/paleontological anatomy. The potential to explain microstructural adaptation is of great interest. However, the determinants of the development of canal orientation remain unclear. Previous studies of birds have shown higher proportions of circumferential canals (called laminarity) in flight bones than in hindlimb bones, and interpreted this as a sign that circumferential canals are a feature for resistance to the torsional loading created by flight. We defined the laminarity index as the percentage of circumferential canal length out of the total canal length. In this study we examined the vascular canal network in the humerus and femur of a sample of 31 bird and 24 bat species using synchrotron micro‐computed tomography (micro‐CT) to look for a connection between canal orientation and functional loading. The use of micro‐CT provides a full three‐dimensional (3D) map of the vascular canal network and provides measurements of the 3D orientation of each canal in the whole cross‐section of the bone cortex. We measured several cross‐sectional geometric parameters and strength indices including principal and polar area moments of inertia, principal and polar section moduli, circularity, buckling ratio, and a weighted cortical thickness index. We found that bat cortices are relatively thicker and poorly vascularized, whereas those of birds are thinner and more highly vascularized, and that according to our cross‐sectional geometric parameters, bird bones have a greater resistance to torsional stress than the bats; in particular, the humerus in birds is more adapted to resist torsional stresses than the femur. Our results show that birds have a significantly ( P = 0.031) higher laminarity index than bats, with birds having a mean laminarity index of 0.183 in the humerus and 0.232 in the femur, and bats having a mean laminarity index of 0.118 in the humerus and 0.119 in the femur. Counter to our expectation, the birds had a significantly higher laminarity index in the femur than in the humerus ( P = 0.035). To evaluate whether this discrepancy was a consequence of methodology we conducted a comparison between our 3D method and an analogue to two‐dimensional (2D) histological measurements. This comparison revealed that 2D methods significantly underestimate ( P < 0.001) the amount of longitudinal canals by an average of 20% and significantly overestimate ( P < 0.001) the laminarity index by an average of 7.7%, systematically mis‐estimating indices of vascular canal orientations. In comparison with our 3D results, our approximated 2D measurement had the same results for comparisons between the birds and bats but found significant differences only in the longitudinal index between the humerus and the femur for both groups. The differences between our 3D and pseudo‐2D results indicate that differences between our findings and the literature may be partially based in methodology. Overall, our results do not support the hypothesis that the bones of flight are more laminar, suggesting a complex relation between functional loading and microstructural adaptation.